The PINNACLE Study: A Double-blind, Randomized, Sham-controlled Study Evaluating the Optilume BPH Catheter System for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia - Kaplan, Steven A.; Moss, Jared; Freedman, Sheldon; Coutinho, Karl; Wu, Ning; Efros, Mitchell; Elterman, Dean; D'Anna, Richard; Padron, Osvaldo; Robertson, Kaiser J.; Lawindy, Samuel; Mistry, Sandeep; et al. (The Journal of urology, 2023)
Purpose:The Optilume BPH Catheter System is a novel drug/device combination minimally invasive surgical therapy for the treatment of lower urinary tract symptoms secondary to benign prostatic hyperplasia. The PINNACLE study is a prospective, randomized, double-blind, sham-controlled clinical trial evaluating the safety and efficacy of Optilume BPH against a sham surgical procedure.Materials and Methods:Eligible patients were men 50 years or older with symptomatic benign prostatic hyperplasia and a prostate size between 20 and 80 g. Subjects were randomized 2:1 to receive treatment with Optilume BPH or a sham surgical procedure. Blinding was maintained for subjects in both arms and evaluating personnel through 1 year postprocedure. Follow-up assessments included the International Prostate Symptom Score, uroflowmetry, and other quality-of-life and sexual function assessments.Results:A total of 148 men were randomized (100 active, 48 sham) at 18 centers in the U.S. and Canada. Subjects randomized to receive Optilume BPH saw a reduction in International Prostate Symptom Score of 11.5±7.8 points at 1 year posttreatment, as compared to a reduction of 8.0±8.3 points at 3 months in the sham arm. Flow rate was dramatically improved after treatment with Optilume BPH, with an improvement of +10.3 mL/s from baseline to 1 year (+125%).Conclusions:Treatment with Optilume BPH provides immediate and sustained improvements in obstructive symptoms and flow rate while preserving erectile and ejaculatory function. Treatment is well tolerated and can be done in an office or ambulatory setting.